Structure, magnetic and electronic transport properties in antiperovskite cubic γ′-CuFe3N polycrystalline films. (June 2020) - Shi, Xiaohui; Li, Xujing; Lai, Zhengxun; Liu, Xiang; Mi, Wenbo
Abstract: The structure, magnetic and electronic transport properties of the facing-target reactively sputtered polycrystalline CuFe3 N films have been investigated systematically. The CuFe3 N film has a cubic antiperovskite structure. The saturation magnetization satisfied the modified Bloch's spin wave theory. At 300 K, the saturation magnetization of the 80 nm-thick CuFe3 N films is 402 emu/cm 3, which is smaller than 800 emu/cm 3 of the 80 nm-thick polycrystalline Fe4 N films. The CuFe3 N films are metallic. The anomalous Hall effect in the "dirty region" of σ xx  < 10 4  S/cm can be explained by the intrinsic mechanism and the side jump in the proper scaling, which is similar to Fe4 N. However, the sign of magnetoresistances in CuFe3 N is opposite to that of Fe4 N below 20 K because the doped-Cu affects the competition among the Lorentz force, spin-orbit coupling, weak localization and s-d exchange interaction. The small anisotropic magnetoresistance is dominated by the spin-down conduction electron. The transformation from the two-fold to one-fold symmetry in the planar Hall resistivity of the 10-nm-thick-CuFe3 N films is related to the competition between the temperature-dependent charge scattering and magnetic-field-dependent spin scattering. Graphical abstract: Image 1 Highlights: The antiperovskite CuFe3 N films with different thicknesses were fabricated on Si and Glass substrate. The anomalous Hall effect whose σ xx falls into the "dirty region" in CuFe3 N can be explained by the proper scaling. The transformation of two-fold to one-fold symmetry in planar Hall resistivity appears. The signs of magnetoresistances in CuFe3 N show an opposite behavior to that in Fe4 N below 20 K.